Syntactic Complexity at the Intermediate Level in EFL Writing by Early Balanced Bilinguals - Grabovac Melisa; Kapranov Oleksandr (East European Journal of Psycholinguistics, 2016)
The present article involves an empirical psycholinguistic study aimed at examining syntactic complexity in English as a Foreign Language (EFL) by early balanced Bosnian/Swedish bilingual EFL learners. 15 early balanced bilingual Bosnian/Swedish EFL learners were recruited for the study and matched with their respective control groups of intermediate EFL learners (15 speakers of Bosnian as their first language (L1) and 15 speakers of Swedish as their L1). The experimental task involved an unprepared writing assignment in English about the most significant invention of the 20th century. The corpus of the participants’ written assignments was analysed in L2 Syntactic Complexity Analyzer and SPSS software programs respectively. Data analysis involved measures of syntactical complexity. It has been found that the participants’ written assignments are characterised by statistically significant number of T-units scores in comparison with the Swedish L1 monolingual controls. These findings are further presented and discussed in the article.ReferencesAhmadian, M. J., & Tavakoli, M. (2011). The effects of simultaneous use of careful onlineplanning and task repetition on accuracy, complexity, and fluency in EFL learners’ oralproduction. Language Teaching Research, 15(1), 35-59.Alotaibi, A. M. (2016). Examining the Learnability of English Relative Clauses: Evidencefrom Kuwaiti EFL Learners. English Language Teaching, 9(2), 57.Bardovi-Harlig, K., & Bofman, T. (1989). Attainment of syntactic and morphologicalaccuracy by advanced language learners. Studies in Second Language Acquisition, 11(01),17-34.Byrnes, H. (2009). Emergent L2 German writing ability in a curricular context: Alongitudinal study of grammatical metaphor. Linguistics and Education, 20(1), 50–66.Ben-Zeev, S. (1977). The influence of bilingualism on cognitive strategy and cognitivedevelopment. Child Development, 48(3), 1009–1018.Bialystok, E. (1988). Levels of bilingualism and levels of linguistic awareness.Developmental Psychology, 24, 560–567.Bialystok, E., Majumder, S., & Martin, M.M. (2003). Developing phonological awareness:Is there a bilingual advantage? Applied Psycholinguistics, 24, 27–44.Cenoz, J. (1998). Beyond bilingualism: multilingualism and multilingual education.Clevedon, England Multilingual MattersCenoz, J. & Valencia, J. (1992). The role of bilingualism in foreign language acquisition:Learning English in the Basque country. Journal of Multilingual and MulticulturalDevelopmentCummins, J. (2000). Language, Power, and Pedagogy: Bilingual Children in theCrossfire. Clevedon, England: Multilingual MattersDaiute, C.A. (1981). Psycholinguistic Foundations of the Writing Process. Research in theTeaching of English, 15, 1, 5–22Dekydtspotter, L., & Renaud, C. (2014). On second language processing and grammaticaldevelopment: The parser in second language acquisition. Linguistic Approaches toBilingualism, 4(2), 131–165.Gaies, S. J. (1979). Linguistic input in formal second language learning: The issues ofsyntactic gradation and readability in ESL materials. TESOL quarterly, 41–50.Gaies, S. J. (1980). T-unit analysis in second language research: Applications, problemsand limitations. TESOL quarterly, 53–60.Grodner, D., Gibson, E., & Tunstall, S. (2002). Syntactic complexity in ambiguityresolution. Journal of Memory and Language, 46(2), 267–295.Grosjean, F. (2008). Studying Bilinguals. Journal of linguistics, 45, 3, 715–719.Herdina, P, & Jessner U. (2000). The dynamics of third language acquisition. In J. Cenozand U. Jessner (eds) English in Europe: The Acquisition of a Third Language, (pp. 84–98).Clevedon: Multilingual Matters.Ho-Peng, L. (1983). Using T-unit measures to assess writing proficiency of university ESLstudents. RELC Journal, 14(2), 35–43.Hunt, K. (1965). Grammatical structures written at three grade levels. NCTE Researchreport, 3. Champaign, IL.Hunt, K. W. (1970). Syntactic maturity in schoolchildren and adults. Monographs of thesociety for research in child development, 35(1), iii–67.Inoue, C. (2016). A comparative study of the variables used to measure syntacticcomplexity and accuracy in task-based research. The Language Learning Journal, 1–19.Iwashita, N. (2006). Syntactic complexity measures and their relation to oral proficiency inJapanese as a foreign language. Language Assessment Quarterly: An InternationalJournal, 3(2), 151–169.Kapranov, O. (2015). Self-Evaluation of Speech Fluency in English as a Second Languageby Korean Exchange Students Studying in Sweden. In L. Szymanski & M. Kuczynski(eds.) Language, Thought and Education: Exploring Networks. (pp. 61–77). Zielona Gora:Oficyna Wydawnicza Uniwersytetu Zielenogorskiego.Kapranov, O. (2013). Beginner Students’ Speech Fluency in a Second LanguageCompared across Two Contexts of Acquisition. In E. Piechurska-Kuciel & E. SzymanskaCzaplak (eds.) Language in Cognition and Affect (pp.81-95). Berlin: Springer.Kobayashi, H., & Rinnert, C. (1992). Effects of First Language on Second LanguageWriting: Translation versus Direct Composition. Language Learning, 42(2), 183–209.Lambert, W.E. (1974). Culture and language as factors in learning and education. Culturalfactors in learning and education. Bellingham, WA: Fifth Western WashingtonSymposium on Learning.Lu, X. (2010). Automatic analysis of syntactic complexity in second language writing,International Journal of Corpus Linguistics, 15(4), 474–496.Macnamara, B. N., & Conway, A. R. (2014). Novel evidence in support of the bilingualadvantage: Influences of task demands and experience on cognitive control and workingmemory. Psychonomic bulletin & review, 21(2), 520–525.Molnár, T. (2011). Second language versus third language acquisition: A comparison ofthe English lexical competence of monolingual and bilingual students. Toronto WorkingPapers in Linguistics, 33(1).Navés, T., Torras, M. R., & Celaya, M. L. (2003). Long-term effects of an earlier start: Ananalysis of EFL written production. Eurosla yearbook, 3(1), 103–129.Norbert, F. (2012). Bilingual competence and bilingual proficiency in child development.Massachusetts: MIT Press.Ortega, L. (2003). Syntactic complexity measures and their relationship to L2 proficiency:A research synthesis of college‐level L2 writing. Applied linguistics, 24(4), 492–518.Shaw, P., & Liu, E. T. K. (1998). What develops in the development of second-languagewriting?. Applied linguistics, 19(2), 225–254.Slavoff, G.R. & Johnson, J. S. (1995). The effects of age and the rate of learning a secondanguage. Studies in Second Language Acquisition, 17 (1), 1–16.Sotillo, S. M. (2000). Discourse functions and syntactic complexity in synchronous andasynchronous communication. Language Learning & Technology, 4(1), 82–119.Weissberg, B. (2000). Developmental relationships in the acquisition of English syntax:writing vs. speech. Learning and Instruction 10, 37–53.Wolfe-Quintero, K., Inagaki, S, & Kim, H-Y. (1998). Second Language Development inWriting: Measures of Fluency, Accuracy and Complexity Honolulu: University of Hawai'i,Second Language Teaching and Curriculum Center.Wolff, D. (2000). Second language writing: a few remarks on psycholinguistic andinstructional issues. Bergische Universita¨t Gesamthochschule Wuppertal: Wuppertal,Germany.Xiaofei, L. (2010). L2 Syntactical Complexity Analyzer. Software program.Yau, M. S., & Belanger, J. (1984). The Influence Mode on the Syntactic Complexity ofEFL Students at Three Grade Levels. TESL Canada Journal, 2(1), 65–77.Youn, S. J. (2014). Measuring syntactic complexity in L2 pragmatic production:Investigating relationships among pragmatics, grammar, and proficiency. System, 42, 270–287.